Global Outlook for Ice and Snow: Chapter 3 - Why are ice and snow changing? - United Nations Environment Programme (United Nations Environment Programme, 2017)
Changes in ice and snow are influenced by variability within the climate system itself and by external factors such as greenhouse gases, solar variability, and volcanic dust – factors that act on time scales from months to hundreds of thousands of years. During the 21st century, the most important external influence on high latitude climate and on ice and snow conditions will be the increase in greenhouse gases. Natural climate variability will still impose regional, decadal, and year-to-year differences, and feedbacks will become increasingly important in the climate system. Before 2050 the ice albedo feedback will accelerate the loss of Arctic sea ice. Warmer temperatures will reduce the area of snow cover and produce an earlier melt in snow-covered regions. This reduced snow cover will itself speed up warming http://www.unep.org/geo/geo_ice/